Oh Canada! Too many children in poverty for too long - Rothman, Laurel (Pulsus Group Inc, 2007)
Despite continued economic growth, Canada’s record on child poverty is worse than it was in 1989, when the House of Commons unanimously resolved to end child poverty by the year 2000. Most recent data indicate that nearly 1.2 million children – almost one of every six children – live in low-income households. Campaign 2000 contends that poverty and income inequality are major barriers to the healthy development of children, the cohesion of our communities and, ultimately, to the social and economic well-being of Canada. Canada needs to adopt a poverty-reduction strategy that responds to the UNICEF challenge to establish credible targets and timetables to bring the child poverty rate well below 10%, as other Organisation for Economic Co-operation and Development nations have done. Campaign 2000 calls on the federal government to develop a cross-Canada poverty-reduction strategy in conjunction with the provinces, territories and First Nations, and in consultation with low-income people. This strategy needs to include good jobs at living wages that ensure that full-time work is a pathway out of poverty; an effective child benefit of $5,100 that is indexed; a system of affordable, universally accessible early learning and child care services available to all families irrespective of employment status; an affordable housing program that creates more affordable housing and helps to sustain existing stock; and affordable and accessible postsecondary education and training programs that prepare youth and adults for employment leading to economic independence.